Modeling habituation of introduced predators to unrewarding bird odors for conservation of ground‐nesting shorebirds. Issue 1 (6th December 2018) - Latham, M. Cecilia; Anderson, Dean P.; Norbury, Grant; Price, Catherine J.; Banks, Peter B.; Latham, A. David M.
Abstract: Foraging mammalian predators face a myriad of odors from potential prey. To be efficient, they must focus on rewarding odors while ignoring consistently unrewarding ones. This may be exploited as a nonlethal conservation tool if predators can be deceived into ignoring odors of vulnerable secondary prey. To explore critical design components and assess the potential gains to prey survival of this technique, we created an individual‐based model that simulated the hunting behavior of three introduced mammalian predators on one of their secondary prey (a migratory shorebird) in the South Island of New Zealand. Within this model, we heuristically assessed the outcome of habituating the predators to human‐deployed unrewarding bird odors before the bird's arrival at their breeding grounds, i.e., the predators were "primed." Using known home range sizes and probabilities of predators interacting with food lures, our model suggests that wide‐ranging predators should encounter a relatively large number of odor points (between 10 and 115) during 27 d of priming when odor is deployed within high‐resolution grids (100–150 m). Using this information, we then modeled the effect of different habituation curves (exponential and sigmoidal) on the probability of predators depredating shorebird nests. Our results show that important gains in nest survival can be achieved regardless of the shape of the habituation curve, but particularly if predators are fast olfactory learners (exponential curve), and even if some level of dishabituation occurs after prey become available. Predictions from our model can inform the amount and pattern in which olfactory stimuli need to be deployed in the field to optimize encounters by predators, and the relative gains that can be expected from reduced predation pressure on secondary prey under different scenarios of predator learning. Habituating predators to odors of threatened secondary prey may have particular efficacy as a conservation tool in areas where lethal predator control is not possible or ethical, or where even low predator densities can be detrimental to prey survival. Our approach is also relevant for determining interaction probabilities for devices other than odor points, such as bait stations and camera traps.